The Impact of Digital Word Wall Use on EFL Learners’ Speaking Proficiency in Secondary Education - Erli Yelvia; Fitrawati Fitrawati (AL-ISHLAH: Jurnal Pendidikan, 2025)
Speaking clearly and effectively is crucial for English as a Foreign Language (EFL) learners, yet limited vocabulary, low confidence, and teacher-centered instruction often hinder oral communication. This study examined the effect of the Wordwall application on secondary students’ speaking ability. A quasi-experimental design was employed with 40 eighth-grade students from a junior secondary school. Two intact classes were assigned as groups: Class 8C (n = 20) as the experimental group and Class 8B (n = 20) as the control group. Students’ speaking performance was measured using an analytical rubric covering pronunciation, grammar, vocabulary, fluency, and comprehension. Data were analyzed using SPSS 20 through normality and homogeneity tests, followed by paired- and independent-samples t-tests. Results indicated a significant difference between groups on post-test scores, t(38) = 3.502, p = .001, with a mean difference of 12.00. The experimental group also showed a significant improvement from pre-test (M = 36.98) to post-test (M = 70.50), t(19) = 25.570, p .001. The findings suggest that integrating Wordwall significantly enhances students’ speaking proficiency. Its interactive features appear to support vocabulary use, fluency, and learner confidence by creating a more engaging and low-anxiety learning environment. Accordingly, incorporating Wordwall into EFL speaking instruction is recommended.